Red Cross Emblem Its Use and Misuse - Shailesh Male; Venkatesh Maled (Al Ameen Medical College, 2012)
Geneva Convention in 1964 initiated the Red Cross movement to help the wounded soldiers. The Red Cross emblem was used during war to rescue workers/soldiers. After that incident soon it became popular and doctors, health workers, paramedical people, chemists etc started using it unofficially. This emblem was derived from color reversal of Swiss national flag to honor the country in which the Red Cross society was originated. Unauthorized use of Red Cross emblem is punishable offence in India U/S 12 r/w 13 under chapter IV of Geneva Convention Law. Since long time doctors are identified by Red Cross